Social Indicators from News-Based Gender Violence Events - Oliveira, Samuel R. S.; Zitei, Daniel; Marcacini, Ricardo M. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2026)
Official indicators are essential for monitoring gender violence, but they often arrive late and provide limited contextual detail about specific events. This paper explores online news as a complementary social sensing layer for producing low-latency indicators of gender violence. We propose a pipeline that collects news reports, retrieves target-related documents, removes duplicates, normalizes temporal and geographic information, and uses language models to classify gender violence events and extract structured metadata. Each event includes attributes such as violence type, location, victim–aggressor relationship, severity, outcome, and event dynamics. Using Brazilian news from 2020 to April 2026 as a case study, we show how structured news-based events can support temporal monitoring, spatial analysis, comparison with official data, and executive summaries of emerging peaks. The results indicate that news can anticipate signals, enrich interpretation, and support public managers with more timely and semantically detailed evidence.